2018
DOI: 10.1177/0300060518771265
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic glioblastoma: commentary and suggested mechanism

Abstract: The role of head trauma in the development of glioblastoma is highly controversial and has been minimized since first put forward. This is not unexpected because skull injuries are overwhelmingly more common than glioblastoma. This paper presents a commentary based on the contributions of James Ewing, who established a major set of criteria for the recognition of an official relationship between trauma and cancer. Ewing’s criteria were very stringent. The scholars who succeeded Ewing have facilitated the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In 1978, Morantz and Shain examined a rat model for neural tumors and found that animals exposed to a cerebral stab wound were more likely to develop gliomas compared with uninjured control animals. Subsequently, a variety of potential mechanisms have been proposed, including alterations in metabolism, inflammation, astrocyte proliferation, and stem cell migration and differentiation . More recently, Richards and colleagues performed single-cell RNA sequencing on glioblastoma stem cells from 26 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In 1978, Morantz and Shain examined a rat model for neural tumors and found that animals exposed to a cerebral stab wound were more likely to develop gliomas compared with uninjured control animals. Subsequently, a variety of potential mechanisms have been proposed, including alterations in metabolism, inflammation, astrocyte proliferation, and stem cell migration and differentiation . More recently, Richards and colleagues performed single-cell RNA sequencing on glioblastoma stem cells from 26 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Philip et al indicated that inflammation, especially TNF-α production, is a tumor promoter in the context of cancer induction [ 25 ]. Ohana et al demonstrated that the transcription factors of the p53, HIF-1a and c-Myc oncogenes play a role in inflammation and in the development of glioblastomas after TBI [ 14 ]. In our previous study, we demonstrated that TBI may activate local and systemic TNF-α production [ 26 28 ]; therefore, we speculate that if the inflammatory response continues and becomes chronic in moderate/severe TBI patients, it will persistently activate transcription factors and increase the probability of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the local effects of a TBI on the brain, TBI may lead to systemic effects by activating neuroinflammation, followed by non-neurological dysfunctions in the cardiovascular system, lungs, liver, gastrointestinal tract, kidneys and neuroendocrine system [ 11 ]. These effects have a similar pathophysiology as carcinogenesis [ 5 7 ], especially the local effect of TBI, which may be related to brain tumors, including benign [ 12 ] and malignant tumors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Injury and inflammation have been associated with various types of cancer or other recurrent trauma. However, its implication in GBM development has not been confirmed by epidemiological studies [94].…”
Section: Inflammatory Reaction At Brain Injury Locationmentioning
confidence: 98%